Patient-reported outcomes in patients with primary immunodeficiency diseases in Japan: baseline results from a prospective observational study - Kanegane, Hirokazu; Ishimura, Masataka; Kawai, Toshinao; Okada, Satoshi; Okamatsu, Nobuaki; Go, Madoka; Noto, Shinichi (Frontiers in Immunology, 2023)
Introduction Primary immunodeficiency diseases (PIDs) are rare inherited diseases resulting in impaired immunity. People with PID experience lower health-related quality of life (HR-QOL) and disease-related burdens in daily activities. This ongoing, prospective observational study aims to evaluate disease activity, treatment status, treatment-related burden, daily activities, and HR-QOL in patients with PID in Japan over a 1-year period. In this interim report (database lock: July 29, 2022), we present baseline results. Methods Participants were enrolled between November 2021 and May 2022; data were collected four times/year per participant until May 2023 using an online electronic patient-reported outcomes system. Patients with PID and healthy volunteers aged ≥12 years, residing in Japan, and with access to a smartphone were eligible. HR-QOL (primary endpoint) was assessed by the EuroQol-5 Dimensions-5 Levels (EQ-5D-5L) and the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). Work productivity was assessed by the Work Productivity and Activity Impairment (WPAI) Questionnaire. Other aspects of PID and burden were assessed with a new questionnaire developed in-house. The study is registered at the University hospital Medical Information Network clinical trials registry (UMIN000045622). Results The full interim analysis set comprised 71 patients with PID and 47 healthy volunteers. The most common International Union of Immunological Societies PID category was primary antibody deficiency (56.3% of patients). Complications were common, especially recurrent respiratory tract infections (63.4%). Most patients with PID were treated with immunoglobulin replacement therapy (73.2%); 22.4% of these patients had serum immunoglobulin levels <700 mg/dL. Among patients who did not undergo hematopoietic cell transplantation, EQ-5D-5L (n=67) and SF-36 (n=59) Physical and Mental Component Summary scores were significantly lower than in healthy volunteers (p < 0.001). WPAI absenteeism, work productivity loss, and activity impairment scores were significantly lower in 42 working patients with PID than in 37 working healthy volunteers (p < 0.05). Other results indicated that patients with PID experience substantial burdens related to medical visits, expenses, work, and daily activities. Discussion This interim analysis confirms that patients with PID in Japan have lower HR-QOL and work productivity compared with healthy individuals and experience substantial limitations and burdens in their daily lives.